Life Cycle Assessment (LCA) Pengelolaan Sampah di TPA Gunung Panggung Kabupaten Tuban, Jawa Timur - Ula, Rahmah Arfiyah; Prasetya, Agus; Haryanto, Iman (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2021)
ABSTRACT The primary municipal waste treatment in Tuban Regency, East Java, was landfilling, besides the small amount of the waste was turned to compost. Landfilling causes global warming, which leads to climate change due to CH4 emission. This environmental impact could be worst by the population growth that increases the amount of waste. This study aimed to evaluate the environmental impact on waste management in the Gunung Panggung landfill in Tuban Regency and its alternative scenarios using Life Cycle Assessment (LCA). Four scenarios were used in this study. They are one existing scenario and three alternative scenarios comprising landfilling, composting, and anaerobic digestion. The scope of this study includes waste transportation to waste treatment which is landfilling, composting, and anaerobic digestion (AD). The functional unit of this analysis is per ton per year of treated waste. Environmental impacts selected are global warming potential, acidification potential, and eutrophication potential. The existing waste management in Gunung Panggung landfill showed the higher global warming potential because of the emission of CO2 and cost for human health, which is 6.379.506,17 CO2 eq/year and 5,92 DALY, respectively. Scenario 3 (landfilling, composting, and AD; waste sortation 70%) showed a lower environmental impact than others, but improvements were still needed. Covering compost pile or controlling compost turning frequency was proposed for scenario 3 amendment. Keywords: environmental impact, landfill, life cycle assessment, waste management Â ABSTRAK Landfill merupakan pengelolaan sampah utama di tempat pemrosesan akhir (TPA) Gunung Panggung Kabupaten Tuban. Selain landfill, pengomposan diterapkan untuk mengolah sebagian kecil sampahnya. Landfill menghasilkan gas metana yang menyebabkan pemanasan global dan memicu perubahan iklim. Pertambahan penduduk memperbanyak sampah yang perlu diolah di TPA dan dapat memperparah dampak lingkungan yang ditimbulkan. Tujuan penelitian ini adalah menilai dampak lingkungan dari pengelolaan sampah eksisting di TPA Gunung Panggung Kabupaten Tuban Jawa Timur beserta skenario alternatifnya menggunakan Life Cycle Assessment (LCA). Terdapat satu skenario eksisting dan tiga skenario alternatif pengelolaan sampah yaitu landfilling, pengomposan, dan fermentasi anaerob (anaerobic digestion). Ruang lingkup studi meliputi pengangkutan sampah, pengelolaan sampah dengan cara pengomposan, Anaerobic Digestion (AD), dan landfill. Satuan fungsional yang digunakan yakni ton sampah yang diolah per tahun. Dampak lingkungan yang dipelajari di antaranya: pemanasan global, asidifikasi, dan eutrofikasi. Dampak lingkungan skenario eksisting menunjukkan nilai tertinggi terutama pada pemanasan global (6.379.506,17 CO2eq/tahun) dan kerugian pada kesehatan manusia (5,92 DALY). Skenario alternatif 3, yang meliputi pengelolaan secara landfill, pengomposan, dan AD menunjukkan dampak lingkungan yang kecil, namun memerlukan perbaikan. Perbaikan untuk skenario 3 yaitu dengan menambahkan penutup pada tumpukan kompos atau mengontrol frekuensi pembalikan kompos untuk mengurangi emisi NH3. Kata kunci: dampak lingkungan, life cycle assessment, pengelolaan sampah, tempat pemrosesan akhir